Communication Theory Of Identity: Artists Becoming Politicians (Case Study Nafa Urbach): Systematic Literature Review - Mubarok, Husni; Syam Maella, Nur’annafi Farni; Abror, Dhimam; Zulaikha, Zulaikha; Harliantara , Harliantara (Jurnal Pendidikan Indonesia, 2025)
This systematic literature review explores the identity transformation of artists transitioning into politics, using Nafa Urbach’s journey as a case study and applying the Communication Theory of Identity (CTI) by Michael Hecht. The study aims to identify key factors influencing this transition, including communication strategies, media portrayals, and public perceptions. Through a comprehensive analysis of scholarly literature, this review examines how artists negotiate their identities across personal, relational, communal, and material frames to gain political legitimacy. The findings indicate that artists must strategically communicate their political agenda and reshape their public image to establish credibility and overcome initial skepticism from both the public and media. Media portrayals significantly influence audience perception, underscoring the need for effective media engagement strategies. The study also highlights the broader implications of identity transformations on political communication dynamics. As artists navigate dual expectations from their entertainment fanbase and politically engaged audiences, maintaining a coherent and relatable identity becomes crucial for political success. The research contributes to a deeper understanding of how communication strategies shape identity negotiation and political acceptance for celebrity politicians. This review offers practical insights for political campaign strategists and media professionals while laying a foundation for future studies on identity formation in political contexts.